Evaluation of the Compton (Incoherent) and Rayleigh (Coherent) Differential Cross Sections of Scattering for Rhodium 103Rh45 and Tantalum181Ta73 by Employing CSC model (Baghdad Science Journal, 2012)
The differential cross section for the Rhodium and Tantalum has been calculated by using the Cross Section Calculations (CSC) in range of energy(1keV-1MeV) . This calculations based on the programming of the Klein-Nashina and Rayleigh Equations. Atomic form factors as well as the coherent functions in Fortran90 language Machine proved very fast an accurate results and the possibility of application of such model to obtain the total coefficient for any elements or compounds.